Blasphemy : A Novel - Durrani, Tehmina (Rawalpindi Ferozsons (Pvt.) Ltd., 1998)
Fictionalized account of a true story of a Muslim woman, victim of disguised evils in Islamic society.
Include Glossary.
English Fiction.
Keywords: Muslim women -- Religious leaders -- Pakistan